Effects of Exercise Intervention on Gross Motor and Social Skills in Children with Autism: A Systematic Review - Jiawei Luo; Ziteng Wang; Yun Li (Ilmu Inovasi Nusantara, 2025)
With the increasing prevalence of autism diagnoses worldwide, there is a growing demand for interventions that support the holistic development of children with autism, particularly in gross motor function and social interaction. While exercise-based interventions have shown promise, existing research presents inconsistent findings. This study aims to systematically review the literature to clarify the potential effects of exercise interventions on the physiological health and social skills of children with autism. The ultimate goal is to derive universal conclusions and inform the development of tailored physical activity curricula that meet the unique needs of autistic children, providing a solid scientific foundation for inclusive physical education practices. A comprehensive literature review was conducted using subject-based searches across multiple databases, including PubMed, CNKI, Wikipedia, Web of Science, and Medline, covering publications from January 2006 to January 2024. After rigorous screening, sixteen randomized controlled trials (RCTs) focusing on exercise interventions for children with autism were selected for analysis. The systematic review revealed that exercise interventions significantly enhance gross motor skills and improve social interaction among children with autism. Additionally, these interventions contribute to improved executive functioning and are effective in reducing anxiety and feelings of low self-worth. Exercise interventions play a critical role in fostering the overall development of children with autism. They not only improve motor proficiency and social engagement but also boost self-confidence and alleviate psychological challenges. These findings underscore the importance of integrating structured physical activity programs into the education and therapy of children with autism to support their physical, emotional, and social well-being